Agritourism and Socioeconomic Potentials of Orchards: A case of Laro Yewa Land Ogun State Southwest Nigeria - Okosodo Ehi Francis (Jurnal Kepariwisataan: Destinasi, Hospitalitas dan Perjalanan, 2024)
This study explores the potential of developing agritourism through orchard management in the Ilaro Yewa Land region of southwestern Nigeria. Utilizing site-to-site observations and semi-structured questionnaires, the research investigates ten selected orchard plantations, focusing on five to ten prevalent fruit tree species within each plantation. Data was collected from 45 staff members involved in various aspects of the orchards. The findings indicate significant potential for orchards to stimulate agritourism, contributing positively to the local economy. Among the respondents, 97.8% agreed that orchards positively impact tourism, while only 2.2% disagreed. The study suggests that integrating agritourism with orchard management can provide additional income for local farmers, create educational opportunities for visitors, and promote sustainable agricultural practices. This approach supports cultural, economic, and environmental sustainability in the Ilaro Yewa Land region. The research concludes that agritourism, centered around orchard management, is viable and beneficial for enhancing the economic welfare of the local community and maintaining the ecological health of the region.